2015
DOI: 10.1002/ejic.201500643
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Protective Effects of Cerium Oxide Nanoparticles (Nanoceria) Depending on Their Preparation Method, Particle Size, Cell Type, and Exposure Route

Abstract: Nanoceria (cerium oxide nanoparticles) toxicity is currently a concern because of its use in motor vehicles in order to reduce carbon monoxide (CO), nitrogen oxides (NOx), and hydrocarbons in exhaust gases. In addition, many questions arise with respect to its biomedical applications exploiting its potential to protect cells against irradiation and oxidative stress. Indeed, toxicology studies on nanoceria report results that seem contradictory, demonstrating toxic effects in some studies, protective effects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 88 publications
1
76
0
1
Order By: Relevance
“…While studies reported that CeO 2 NPs have antioxidant properties and protect against oxidative stress induced by cigarette smoke and X-ray radiation, as well as, in animal models, ischemia/reperfusion, stroke, and neurodegeneration, other studies have, however, reported that these nanoparticles cause oxidative stress both in vivo following pulmonary exposure and in vitro in human monocytes [44]. The reason behind these discrepancies could be related to the preparation methods of CeO 2 NPs, the pH of the biological milieu in which the nanoparticles are tested, the particle size, the cell types, and the route of exposure [44]. Our data show that, as a consequence of the route of exposure to CeO 2 NPs, that is, through the lung, all the markers of oxidative stress assessed were affected in the lung tissue.…”
Section: Discussionmentioning
confidence: 99%
“…While studies reported that CeO 2 NPs have antioxidant properties and protect against oxidative stress induced by cigarette smoke and X-ray radiation, as well as, in animal models, ischemia/reperfusion, stroke, and neurodegeneration, other studies have, however, reported that these nanoparticles cause oxidative stress both in vivo following pulmonary exposure and in vitro in human monocytes [44]. The reason behind these discrepancies could be related to the preparation methods of CeO 2 NPs, the pH of the biological milieu in which the nanoparticles are tested, the particle size, the cell types, and the route of exposure [44]. Our data show that, as a consequence of the route of exposure to CeO 2 NPs, that is, through the lung, all the markers of oxidative stress assessed were affected in the lung tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Tarnuzzer's group found that nanoceria exhibited radioprotection of normal human breast epithelial cells, but not to MCF-7 cancer cells for the first time [24]. In addition, the size, shape, agglomeration state, surface charge, and surface modification of nanoceria together determine its bioresponse to cancer cells [41][42][43][44]. Dextran-coated nanoceria prepared by Alili et al [45] has been used to prevent myofibroblast formation and tumor invasion in tumor-stroma interaction.…”
Section: Targeted Drug and Photodynamic Therapymentioning
confidence: 99%
“…[1][2][3][4][5] In general, cerium can exist in two oxidation states: Ce 3+ and Ce 4+ . Therefore, cerium dioxide can have two different oxide forms, CeO 2 (Ce 4+ ) or Ce 2 O 3 (Ce 3+ ), in bulk material.…”
Section: Introductionmentioning
confidence: 99%
“…1,36 Recently, biosynthesis of NPs using yeast and fungi has also been noted. Munusamy et al had explained rapid and extracellular synthesis of cerium oxide NPs using fungus Curvularia lunata culture media.…”
mentioning
confidence: 99%